Information security and interference immunity of telecommunication systems under conditions of various internal and external impacts - Горбенко, И.Д.; Замула, А.А.; Морозов, В.Л. (Radiotekhnika, 2017)
The problems of increasing noise immunity (stealth operation of the system, noise immunity of signal reception), information security of telecommunication systems (TCS) in the presence of a lot of interference and deliberate influence of counteraction stations are considered. It is shown that this problem solution is possible on the basis of improving the methodological foundations of the TCS construction by developing methods of information exchange, the synthesis of new classes of nonlinear discrete complex signals with the necessary ensemble, correlation and structural properties.